2017
DOI: 10.3349/ymj.2017.58.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically Documented Macular Ischemia after Single Bevacizumab for Macular Edema Secondary to Central Retinal Vein Occlusion

Abstract: This report describes a case of angiographically documented foveal avascular zone (FAZ) enlargement after a single intravitreal injection of bevacizumab for macular edema secondary to central retinal vein occlusion (CRVO). A 71-year-old female was treated with an intravitreal bevacizumab injection for macular edema following CRVO. Despite successfully decreased edema one month after injection, the postinjection best-corrected visual acuity immediately decreased from 20/40 to 20/1000 (Snellen equivalent). The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Animal models suggest that anti-VEGF treatment is associated with retinal capillary loss [11, 12]. Furthermore, numerous case reports have correlated increased retinal non-perfusion with anti-VEGF injections in Retinal Vein Occlusion (RVO) and DME [1315]. Nevertheless, Campochiaro et al showed that elevated VEGF levels were associated with capillary non-perfusion, and eyes treated with anti-VEGF antibodies for RVO/DME had reduced rates of development of capillary non-perfusion [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest that anti-VEGF treatment is associated with retinal capillary loss [11, 12]. Furthermore, numerous case reports have correlated increased retinal non-perfusion with anti-VEGF injections in Retinal Vein Occlusion (RVO) and DME [1315]. Nevertheless, Campochiaro et al showed that elevated VEGF levels were associated with capillary non-perfusion, and eyes treated with anti-VEGF antibodies for RVO/DME had reduced rates of development of capillary non-perfusion [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, after anti-VEGF treatment, 24 highly expressed biomarkers were reported to normalize toward an unequivocal trend in aqueous of various ocular VEGF-related conditions ( Sharma et al, 2010 ). However, not all patients show full response to anti-VEGF therapy ( Ashraf et al, 2016 ), and even some studies report that prolonged injections of anti-VEGF agents may aggravate retinal ischemia ( Toy et al, 2016 ; Lee et al, 2017 ), attribute to the irreversible degradation of retinal neurons and retinal pigment epithelium (RPE) ( Ashraf et al, 2016 ; Gemenetzi et al, 2017 ; Keir et al, 2017 ), and increase the incidence of retinal fibrosis and tractional retinal detachment ( Hu et al, 2014 ). Aflibercept is a recombinant human fusion protein that works as a soluble decoy receptor that binds to VEGF family members, including VEGF-A, VEGF-B, and placental growth factor (PIGF), to block their activities.…”
Section: Introductionmentioning
confidence: 99%
“…While anti‐VEGF agents represent a major breakthrough in the treatment of retinal diseases with an angiogenic component, they have been used with limited success (Usui et al, ). Not all patients respond to anti‐VEGF treatment (Ashraf, Souka, Adelman, & Forster, ; Chin‐Yee, Eck, Fowler, Hardi, & Apte, ) and increasing evidence suggests that, in some cases, prolonged treatment with anti‐VEGF may lead to hypoxia, exacerbate retinal ischemia (Lee, Kang, & Koh, ; Toy, Schachar, Tan, & Moshfeghi, ) and lead to degeneration of retinal neurons and retinal pigment epithelium (RPE) (Ashraf et al, ; Gemenetzi et al, ; Keir et al, ). Thus, there is a large unmet medical need to develop new, targeted therapies that will either improve efficacy or reduce off‐target effects when used in combination with anti‐VEGF drugs.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF may lead to hypoxia, exacerbate retinal ischemia (Lee, Kang, & Koh, 2017;Toy, Schachar, Tan, & Moshfeghi, 2016) and lead to degeneration of retinal neurons and retinal pigment epithelium (RPE) (Ashraf et al, 2016;Gemenetzi et al, 2017;Keir et al, 2017). Thus, there is a large unmet medical need to develop new, targeted therapies that will either improve efficacy or reduce off-target effects when used in combination with anti-VEGF drugs.…”
mentioning
confidence: 99%